A comprehensive phase, minero-chemical and microstructural investigation of low-grade manganese ore. (16th October 2019) - Ali, Sajjad; Iqbal, Yaseen; Fahad, Muhammad
Abstract: Manganese is an important industrial mineral and high-grade manganese ore deposits are constantly diminishing due to its widespread industrial use. Consequently, attempts are being made to develop economically feasible routes to upgrade low-grade manganese ores (LGMO). This requires an in-depth characterization of LGMO before accessing its suitability for up-gradation; therefore, this study pertains to a comprehensive phase, minero-chemical and microstructural characterization of LGMO. The mineral phases observed in the investigated samples included spessartine, pyrolusite, hausmannite, hematite, quartz, and calcite. XRF revealed the presence of 24.17 wt% MnO2 along with SiO2, CaO, Fe2 O3, and Al2 O3 in varying concentrations. TEM revealed trilling intergrown ∼400 nm elongated nano-rods in different directions forming a layered structure. FTIR revealed the presence of pyrolusite evidenced by the Mn-O stretching bands observed at 697, 721 and 1091 cm −1 along with a quartz band at 778 cm −1 . The current results constitute a base to explore suitable methods for upgradation of these virgin LGMO deposits.